Evolutionary recruitment of flexible Esrp-dependent splicing programs into diverse embryonic morphogenetic processes. Issue 1 (December 2017) - Burguera, Demian; Marquez, Yamile; Racioppi, Claudia; Permanyer, Jon; Torres-Méndez, Antonio; Esposito, Rosaria; Albuixech-Crespo, Beatriz; Fanlo, Lucía; D'Agostino, Ylenia; Gohr, Andre; Navas-Perez, Enrique; Riesgo, Ana; et al.
Abstract Epithelial-mesenchymal interactions are crucial for the development of numerous animal structures. Thus, unraveling how molecular tools are recruited in different lineages to control interplays between these tissues is key to understanding morphogenetic evolution. Here, we studyEsrp genes, which regulate extensive splicing programs and are essential for mammalian organogenesis. We find thatEsrp homologs have been independently recruited for the development of multiple structures across deuterostomes. AlthoughEsrp is involved in a wide variety of ontogenetic processes, our results suggest ancient roles in non-neural ectoderm and regulating specific mesenchymal-to-epithelial transitions in deuterostome ancestors. However, consistent with the extensive rewiring ofEsrp -dependent splicing programs between phyla, most developmental defects observed in vertebrate mutants are related to other types of morphogenetic processes. This is likely connected to the origin of an event inFgfr, which was recruited as anEsrp target in stem chordates and subsequently co-opted into the development of many novel traits in vertebrates. Epithelial-mesenchymal interplays are essential to many ontogenetic processes in vertebrates. Here Burgueraet al . show diverse embryonic morphogenetic processes regulated by Epithelial Splicing Regulatory Protein (Esrp ) in different deuterostome species.